We used to live here ebook A novel. - Kliewer, Marcus (2024)
From an author "destined to become a titan of the macabre and unsettling" (Erin A. Craig, #1 New York Times bestselling author), a haunting debut— soon to be a Netflix original movie—about two homeowners whose lives are turned upside down when the house's previous residents unexpectedly visit. As a young, queer couple who flip houses, Charlie and Eve can't believe the killer deal they've just gotten on an old house in a picturesque neighborhood. As they're working in the house one day, there's a knock on the door. A man stands there with his family, claiming to have lived there years before and asking if it would be alright if he showed his kids around. People pleaser to a fault, Eve lets them in. As soon as the strangers enter their home, inexplicable things start happening, including the family's youngest child going missing and a ghostly presence materializing in the basement. Even more weird, the family can't seem to take the hint that their visit should be over. And when Charlie suddenly vanishes, Eve slowly loses her grip on reality. Something is terribly wrong with the house and with the visiting family—or is Eve just imagining things? This unputdownable and spine-tingling novel "is like quicksand: the further you delve into its pages, the more immobilized you become by a spiral of terror. We Used to Live Here will haunt you even after you have finished it" (Agustina Bazterrica, author of Tender Is the Flesh ).